Resveratrol protects against cadmium‐induced cerebrum toxicity through modifications of the cytochrome P450 enzyme system in microsomes - Lv, Mei‐Wei; Zhang, Cong; Ge, Jing; Sun, Xiao‐Han; Li, Jin‐Yang; Li, Jin‐Long (Journal of the science of food and agriculture, 2023)
BACKGROUND Cadmium (Cd), known as a vital contaminant in the environment, penetrates the blood–brain barrier and accumulates in the cerebrum. Acute toxicosis of Cd, which leads to lethal cerebral edema, intracellular accumulation and cellular dysfunction, remains to be illuminated with regard to the exact molecular mechanism of cerebral toxicity. Resveratrol (RES), present in the edible portions of numerous plants, is a simply acquirable and correspondingly less toxic natural compound with neuroprotective potential, which provides some theoretical bases for antagonizing Cd‐induced cerebral toxicity. RESULTS This work was executed to research the protective effects of RES against Cd‐induced toxicity in chicken cerebrum. Markedly, these lesions were increased in the Cd group, which also exhibited a thinner cortex, reduced granule cells, vacuolar degeneration, and an enlarged medullary space in the cerebrum. Furthermore, Cd induced CYP450 enzyme metabolism disorders by disrupting the nuclear xenobiotic receptor response (NXRs), enabling the cerebrum to reduce the ability to metabolize exogenous substances, eventually leading to Cd accumulation. Meanwhile, accumulated Cd promoted oxidative damage and synergistically promoted the damage to neurons and glial cells. CONCLUSION RES initiated NXRs (especially for aromatic receptor and pregnancy alkane X receptor), decreasing the expression of CYP450 genes, changing the content of CYP450, maintaining CYP450 enzyme normal activities, and exerting antagonistic action against the Cd‐induced abnormal response of nuclear receptors. These results suggest that the cerebrum toxicity caused by Cd was reduced by pretreatment with RES. © 2023 Society of Chemical Industry.